Prediksi Data Produksi Menggunakan Regresi Linear Sederhana - Napitupulu, Segar; Siagian, Novriadi Antonius (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
PT. XYZ is a company engaged in the cold forging of automotive metal parts specialists. Companies must meet distribution needs and are required to make the right decisions in determining production strategies. To do this, companies need quite a lot of information sources to be analyzed further. Which, companies also face difficulties in obtaining strategic information such as sales levels per period or best-selling products. The analytical method uses simple linear regression in the prediction system because simple linear regression analysis can predict time series. The results of the analysis on the Collar 17x10.5x11 product were obtained from predictions from January to December 2020 with an error rate of 3.78%. The Nut AM M12x14x12 product obtained prediction results from January to December 2020 with a rate of 12.53%. The Collst product 23.6x16.3x3 obtained prediction results from January to December 2020 with a rate of 5.43%. For Nipple products from January to December 2020 with a rate of 12.14%